Oriented alumina laminate-type polycrystal spinel ceramic sintered body and manufacturing method thereof, optical window material, infrared sensor using the same, and filter
Patent Information
- Application Number
- JP2022077295
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-05-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-05-10
AI Technical Summary
Existing spinel/alumina laminated transparent composite ceramics face limitations in achieving both high visible light transmission and mechanical strength, particularly when attempting to increase the thickness of the alumina layer, which degrades transmission characteristics.
An oriented alumina laminated polycrystalline spinel ceramic sintered body is developed with controlled porosity, grain size, and crystal orientation, where the alumina ceramic is bonded to polycrystalline spinel ceramic, ensuring specific crystal orientations of alumina grains relative to the joint surface, achieved through a manufacturing process involving magnetic field application during alumina slurry molding and sintering at specific temperatures.
The solution results in a ceramic body with excellent visible to mid-infrared transmittance and high mechanical strength, suitable for optical window materials and infrared sensors, maintaining transparency and strength even with thicker alumina layers.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to an oriented alumina stacked polycrystalline spinel ceramic sintered body, a method for manufacturing the same, an optical window material, an infrared sensor using the same, and a filter. [Background technology]
[0002] Alumina (Al2O3), magnesium aluminate (spinel, MgAl2O4), aluminum oxynitride (AlON:Al 23 O 27 Infrared (IR) transparent ceramics such as N5 and yttria (Y2O3) are attracting attention due to their excellent transmittance and high chemical stability in the visible to mid-infrared wavelength range. Among these, spinel exhibits excellent broadband transmittance from visible to mid-infrared, and is expected to be applied to optical window materials and filters for visible light image sensors and infrared sensors.
[0003] Recently, a spinel / alumina laminated transparent composite ceramic has been developed that combines transparency and high hardness by laminating a thin alumina layer on a spinel (see, for example, Non-Patent Document 1). However, in the spinel / alumina laminated transparent composite ceramic described in Non-Patent Document 1, the thickness of the alumina layer is thin, about 300 nm, and it cannot be made thicker because it reduces the transparency in the visible light region. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] L. Liu et al., Scripta Materialia, 205, 2021, 114205 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] Therefore, the object of the present invention is to provide an oriented alumina laminated polycrystalline spinel ceramic sintered body having high visible light transmission characteristics, a method for manufacturing the same, an optical window material, an infrared sensor using the same, and a filter. [Means for solving the problem]
[0006] The oriented alumina laminated polycrystalline spinel ceramic sintered body according to the present invention comprises a polycrystalline spinel ceramic and an alumina ceramic located on the polycrystalline spinel ceramic and bonded to the polycrystalline spinel ceramic, wherein the porosity of the polycrystalline spinel ceramic is less than 0.3%, the grain size of the crystal grains of the polycrystalline spinel ceramic is in the range of 215 nm to 380 nm, the porosity of the alumina ceramic is 0.07% or less, and the grain size of the crystal grains of the alumina ceramic is 320 nm. The wavelength range is from m to 680 nm. When the orientation relationship of the alumina ceramics is measured by electron beam backscatter diffraction (EBSD), the orientation distribution of the crystal grains of the alumina ceramics has a peak due to a specific crystal orientation of the crystal grains of the alumina ceramics being oriented in the range of 0° to 90° with respect to the bonding surface with the polycrystalline spinel ceramics. More than 50% of the crystal grains of the alumina ceramics oriented in the specific crystal orientation are located within ±20° of the position of the peak, thereby solving the above problem. The porosity of the polycrystalline spinel ceramic may be in the range of 0.05% to 0.2%. The porosity of the polycrystalline spinel ceramic may be in the range of 0.1% to 0.2%. The porosity of the alumina ceramics may be in the range of 0.04% to 0.07%. The grain size of the crystal grains of the polycrystalline spinel ceramic may be in the range of 230 nm to 365 nm. The grain size of the alumina ceramics may be in the range of 340 nm to 660 nm. When the thickness of the alumina ceramic is 900 μm, the linear transmittance of light having a wavelength of 500 nm in the polycrystalline spinel ceramic may be 13% or more. When the thickness of the alumina ceramic is 900 μm, the total transmittance of light with a wavelength of 5 μm in the polycrystalline spinel ceramic may be 65% or more. The orientation distribution of the crystal grains of the alumina ceramics may have peaks at 0° or 90° with respect to the bonding surface with the polycrystalline spinel ceramics. The peak intensity ratio I between the (006) plane and the (110) plane in the X-ray diffraction pattern of the surface of the alumina ceramics 006 / I 110 It may be in the range of 0.5 or more and 0.7 or less. The material comprises further alumina ceramics, wherein the further alumina ceramics are bonded to the polycrystalline spinel ceramics on the side facing the alumina ceramics, the porosity of the further alumina ceramics is 0.07% or less, the grain size of the further alumina ceramics is in the range of 320 nm to 680 nm, and when the orientation relationship of the further alumina ceramics is measured by electron beam backscatter diffraction (EBSD), the orientation distribution of the crystal grains of the further alumina ceramics has a peak due to a specific crystal orientation of the crystal grains of the further alumina ceramics being oriented in the range of 0° to 90° with respect to the bonding surface with the polycrystalline spinel ceramics, and 50% or more of the crystal grains of the further alumina ceramics oriented in the specific crystal orientation may be present within ±20° of the position of the peak. The manufacturing method of the above-described oriented alumina laminated polycrystalline spinel ceramic sintered body according to the present invention includes compacting a polycrystalline spinel raw material powder to form a polycrystalline spinel compact, dispersing an alumina raw material powder in a dispersion medium to prepare an alumina raw material slurry, forming the alumina raw material slurry while applying a magnetic field to form an alumina compact, laminating the polycrystalline spinel compact and the alumina compact to form a laminate, and sintering the laminate in a temperature range higher than 1175 °C and not higher than 1500 °C, thereby solving the above problems. The forming of the alumina compact may be performed by slip casting or electrophoretic deposition method. The laminate may be a polycrystalline spinel compact sandwiched between a pair of alumina compacts. The densities of the polycrystalline spinel compact and the alumina compact may be in the range of 40% or more and 70% or less. The sintering may be performed by sintering the laminate in a temperature range of 1220 °C or more and 1300 °C or less. The optical window material according to the present invention is composed of the above-described oriented alumina laminated polycrystalline spinel ceramic sintered body, thereby solving the above problems. The infrared sensor according to the present invention includes the above-described optical window material, thereby solving the above problems. The filter according to the present invention is composed of the above-described oriented alumina laminated polycrystalline spinel ceramic sintered body, thereby solving the above problems.
Advantages of the Invention
[0007] [[ID=ID=20]] [[ID=ID=21]]The oriented alumina laminated polycrystalline spinel ceramic sintered body of the present invention includes polycrystalline spinel ceramics having a predetermined porosity and particle size, and alumina ceramics having a predetermined porosity and particle size located thereon and joined thereto. Since it includes polycrystalline spinel, it has excellent broadband permeability from visible to mid-infrared. Further, by joining with alumina ceramics, the alumina laminated polycrystalline spinel ceramic sintered body of the present invention has excellent mechanical properties and can also improve mechanical strength at the same time.
[0008] In particular, when measuring the orientation relationship of alumina ceramics by the electron backscatter diffraction (EBSD) method, in the oriented alumina laminated polycrystalline spinel ceramic sintered body of the present invention, the orientation distribution of the crystal grains of the alumina ceramics has a peak due to the specific crystal orientation of the crystal grains of the alumina ceramics being oriented in the range of 0° or more and 90° or less with respect to the bonding surface with the spinel ceramics, and it is controlled such that 50% or more of the crystal grains of the alumina ceramics oriented in a specific crystal orientation exist within the range of ±20° of the peak position. Thus, since the alumina ceramics have a predetermined orientation, it is possible to improve visible light transmittance while maintaining high mechanical strength. Such an oriented alumina laminated polycrystalline spinel ceramic sintered body can be used for optical window materials such as infrared sensors and filters for infrared laser communication and detection applications.
[0009] The manufacturing method of the oriented alumina laminated polycrystalline spinel ceramic sintered body of the present invention includes sintering a laminate of a compacted polycrystalline spinel formed body and an alumina formed body formed in a magnetic field in a temperature range higher than 1175°C and lower than or equal to 1500°C. By simply controlling the direction of the magnetic field during manufacturing, the above-mentioned oriented alumina laminated polycrystalline spinel ceramic sintered body can be obtained.
Brief Description of the Drawings
[0010] [Figure 1] Schematic diagram showing the oriented alumina laminated polycrystalline spinel ceramic sintered body of the present invention [Figure 2] Schematic diagram showing an exemplary orientation distribution of alumina crystal grains in the oriented alumina laminated polycrystalline spinel ceramic sintered body of the present invention [Figure 3] Flowchart showing the manufacturing process of the oriented alumina laminated polycrystalline spinel ceramic sintered body of the present invention [Figure 4] Schematic diagram showing an infrared sensor using the alumina laminated polycrystalline spinel ceramic sintered body of the present invention [Figure 5] Procedure showing a part of the manufacturing process of the sample of Example 2 [Figure 6] Figure showing SEM images of cross-sections of the samples from Example 2 and Example 8. [Figure 7] Figure showing the SEM image of the sample in Example 2. [Figure 8] Figure showing the SEM image of the sample in Example 8. [Figure 9] Figure showing EBSD mapping of samples in Example 2, Example 8, and Example 14. [Figure 10] Figure 9 shows the orientation distribution of the crystal grains. [Figure 11] Figure showing the XRD patterns of samples in Examples 2, 8, and 13. [Figure 12] Figure showing the linear transmittance spectra of various samples in visible light. [Figure 13] Figure showing infrared transmittance spectra of various samples. [Figure 14] Figure showing infrared transmittance spectra of various samples. [Figure 15] A diagram showing the relationship between transmittance and the intensity ratio of X-ray diffraction. [Modes for carrying out the invention]
[0011] Embodiments of the present invention will be described below with reference to the drawings. Similar elements will be given the same numbers, and their descriptions will be omitted.
[0012] (Embodiment 1) Embodiment 1 describes the oriented alumina-layered polycrystalline spinel ceramic sintered body and the method for producing the same according to the present invention. In this specification, the visible to infrared region refers to the range of 500 nm to 5 μm, and the linear transmittance (T) at a wavelength of 500 nm is defined as the thickness direction of a sintered body having alumina ceramics with a thickness of 900 μm. in(500nm) A value of 10% or more is considered to indicate excellent visible transmittance, and the total transmittance (T) at a wavelength of 5 μm is also considered to be excellent. total(5μm)A value of 60% or more is considered to indicate excellent infrared transmittance. Furthermore, the "boundary of linear transmittance at a wavelength of 500 nm being 10%" is based on the minimum characteristics necessary for visually confirming the object, and the "boundary of total transmittance at a wavelength of 5 μm being 60%" is based on the minimum characteristics necessary for various detections, taking into account attenuation due to the influence of the atmospheric environment.
[0013] Furthermore, high hardness (Hv) is defined in the Vickers hardness test, using the diagonal length (a) of the indentation when a load of 2N is applied for 15 seconds, as follows: Hv = 0.1891(2 / a) 2 This refers to a hardness of 23 GPa or higher, as determined from the formula.
[0014] Figure 1 is a schematic diagram showing the oriented alumina layered polycrystalline spinel ceramic sintered body of the present invention.
[0015] The oriented alumina laminated polycrystalline spinel ceramic sintered body 100 of the present invention (hereinafter referred to as the sintered body 100 of the present invention for simplicity) comprises a polycrystalline spinel ceramic 110 and an alumina ceramic 120 located thereon and bonded to the polycrystalline spinel ceramic 110.
[0016] The polycrystalline spinel ceramics 110 and the alumina ceramics 120 are bonded and integrated, and preferably, there is no second phase at the bonding interface. Therefore, the sintered body 100 of the present invention has excellent overall mechanical strength. However, there may be changes in the composition of the alumina or polycrystalline spinel at the bonding interface. The absence of a second phase can be determined from the SEM image, and the change in composition can be determined from the profile obtained by an energy-dispersive X-ray spectrometer (EDS).
[0017] Furthermore, in the sintered body 100 of the present invention, the porosity of the polycrystalline spinel ceramics 110 is controlled to less than 0.3%. This results in an extremely dense sintered body with excellent visible light transmission. There is no particular lower limit, and the porosity may be 0%, but less than 0.3% is acceptable.
[0018] The porosity of the polycrystalline spinel ceramics 110 preferably satisfies the range of 0.05% to 0.2%. This results in a dense sintered body with excellent visible and infrared transmittance.
[0019] The porosity of the polycrystalline spinel ceramics 110 is more preferably in the range of 0.1% to 0.2%. This results in a dense sintered body with excellent visible and infrared transparency and mechanical strength.
[0020] Furthermore, in the sintered body 100 of the present invention, the porosity of the alumina ceramics 120 is controlled to 0.07% or less. This results in an extremely dense sintered body that maintains mechanical strength. There is no particular lower limit, and the porosity may be 0%, but 0.07% or less is acceptable.
[0021] The porosity of the alumina ceramics 120 preferably satisfies the range of 0.04% to 0.07%. This results in a dense sintered body with excellent mechanical strength.
[0022] The porosity of the alumina ceramics 120 is more preferably in the range of 0.045% to 0.065%. This results in a dense sintered body with even better visible / infrared transparency and mechanical strength.
[0023] The porosity of polycrystalline spinel ceramics 110 and alumina ceramics 120 was calculated from the ratio of pore area per unit area obtained from microstructure images using a scanning electron microscope (SEM).
[0024] In the sintered body 100 of the present invention, the particle size of the polycrystalline spinel ceramics 110 is in the range of 215 nm to 380 nm. This provides the polycrystalline spinel ceramics 110 with excellent visible light transmittance. Preferably, the particle size of the polycrystalline spinel ceramics 110 is in the range of 230 nm to 365 nm. This provides the polycrystalline spinel ceramics 110 with excellent mechanical strength while maintaining visible and infrared transmittance. More preferably, the particle size of the polycrystalline spinel ceramics 110 is in the range of 230 nm to 260 nm.
[0025] In the sintered body 100 of the present invention, the particle size of the alumina ceramics 120 is in the range of 320 nm to 680 nm. This further improves the mechanical strength of the alumina ceramics 120. Preferably, the particle size of the alumina ceramics 120 is in the range of 340 nm to 660 nm. This further improves the mechanical strength of the alumina ceramics 120. More preferably, the particle size of the alumina ceramics 120 is in the range of 340 nm to 400 nm. This further improves the mechanical strength of the alumina ceramics 120 while maintaining transparency.
[0026] In this specification, the particle size in the sintered body was calculated from the number of particles per unit area using electron microscopy (e.g., scanning electron microscope (SEM) images). Specifically, the apparent average particle diameter of the crystal grains was measured from an SEM image of the mirror-polished surface of the sintered body, and this value was multiplied by a coefficient of 1.225 determined based on quantitative morphology to calculate the particle size. The average particle diameter was the average value obtained from 100 or more crystal grains.
[0027] In the sintered body 100 of the present invention, the crystal orientation of the crystal grains 130 of the alumina ceramics 120 is oriented with respect to the bonding surface with the polycrystalline spinel ceramics 110. As schematically shown in Figure 1, the crystal grains of the alumina ceramics 120 are single crystals having a hexagonal crystal structure (specifically, belonging to the R-3c space group (No. 167 in the International Tables for Crystallography)). By bonding such oriented alumina ceramics, in which the crystal grains are oriented in a specific crystal orientation (in this case, oriented in the c-axis direction), to the polycrystalline spinel ceramics 110, it is possible to improve visible light transmission while maintaining high mechanical strength. The specific crystal orientation may be in the a-axis direction other than the c-axis direction.
[0028] As shown in Figure 1, the c-plane of the oriented alumina ceramic 120A, which is oriented in the c-axis direction, may be joined so that it is approximately parallel to the joining surface of the polycrystalline spinel ceramic 110, or the c-plane of the oriented alumina ceramic 120B may be joined so that it is approximately perpendicular to the joining surface of the polycrystalline spinel ceramic. In Figure 1, for simplicity, both the oriented alumina ceramic 120A and 120B are shown as being oriented along the c axis, but the crystal orientation is not limited to this.
[0029] Figure 2 is a schematic diagram showing an exemplary grain orientation distribution of alumina in the oriented alumina-layered polycrystalline spinel ceramic sintered body of the present invention.
[0030] This will be explained in detail. When the orientation relationship of the alumina ceramics 120 of the oriented alumina layered polycrystalline spinel ceramic sintered body 100 described above is measured by electron beam backscatter diffraction (EBSD), it is sufficient that the orientation distribution of the crystal grains of the alumina ceramics has a peak. Such a peak is caused by the orientation of a specific crystal grain 130 of the alumina ceramics 120 being oriented in a range of 0° to 90° with respect to the bonding surface with the polycrystalline spinel ceramics 110.
[0031] For example, as shown by the solid line in FIG. 2, when having a peak at 0°, it can be determined that the c-plane of the c-axis-oriented oriented alumina ceramics 120A (FIG. 1) is joined so as to be substantially parallel to the joint surface of the polycrystalline spinel ceramics 110. Alternatively, as shown by the dotted line in FIG. 2, when having a peak at 90°, it can be determined that the c-plane of the c-axis-oriented oriented alumina ceramics 120B is joined so as to be substantially perpendicular to the joint surface of the polycrystalline spinel ceramics. When the alumina ceramics are random (non-oriented), no peak is shown as indicated by the dashed-dotted line. In the present specification, if 50% or more of the crystal grains exist within the range of ±20% of the peak position, it is considered that the crystal grains are oriented with respect to the joint surface. Although FIG. 2 shows only the cases of 0° and 90°, in the manufacturing method described later, by controlling the direction of application of the magnetic field, it can be oriented at any angle of 0° or more and 90° or less.
[0032] The inventors of the present application have discovered that by forming a laminate in which the oriented alumina ceramics 120 oriented with respect to the polycrystalline spinel ceramics 11 are joined in this way, while maintaining high visible light transmittance, the mechanical strength can be further improved. Since spinel is cubic, the coefficient of thermal expansion (for example, 7.45×10 -6 K -1 @673 K, M. Posarac et al., Sci. Sinter., 41 (2009), pp75 - 81) does not change regardless of the crystal orientation. On the other hand, since alumina is hexagonal, the coefficient of thermal expansion varies depending on the crystal orientation, and it is known that the coefficient of thermal expansion of the c-axis is larger than that of the a-axis (for example, a-axis; 7.04×10 -6 K -1 @673 K, c-axis; 7.68×10 -6 K -1 @673 K, G. Grabowski et al., Archives of Civil and Mechanical Engineering 18 (2008) 188 - 197).
[0033] Therefore, in order to improve mechanical strength, it is common practice to make the thermal expansion coefficients of the ceramics being joined equal in order to minimize the generation of residual stress. From this perspective, it is preferable to use polycrystalline alumina ceramics in which the a-axis and c-axis of the crystal grains are randomly arranged, and to use the average of the a-axis and c-axis coefficients. However, in reality, it has been found that joining oriented alumina ceramics is advantageous in improving mechanical strength, regardless of the magnitude of the difference in thermal expansion coefficient with spinel. Furthermore, surprisingly, it has been found that the orientation does not matter, as the c-axis of the alumina can be parallel or perpendicular to the bonding surface with spinel, contradicting previous common sense.
[0034] When the peak position of the alumina ceramic 120 is 0° or 90°, more preferably, the peak intensity ratio I of the (006) plane and the (110) plane in the X-ray diffraction pattern of the surface of the alumina ceramic 120. 006 / I 110 This satisfies the range of 0.5 to 0.7. As a result, a sintered body 100 with excellent orientation is obtained, which can have high visible light transmittance and high mechanical strength. The orientation and orientation relationship of the alumina ceramics 120 can be determined by the EBSD method, and by referring to the peak intensity ratio described above, it can be determined that the c-plane of the oriented alumina ceramics 120A (Figure 1), which is oriented in the c-axis direction by X-ray diffraction, is bonded to the polycrystalline spinel ceramics 110 in such a way that it is approximately parallel to the bonding surface.
[0035] The sintered body 100 of the present invention can preferably have a linear transmittance of 13% or more for light with a wavelength of 500 nm when the alumina ceramic 120 has a thickness of 900 μm, by controlling the porosity and the grain size and orientation of the crystal grains. More preferably, the sintered body 100 of the present invention can have a linear transmittance of 20% or more. Naturally, the upper limit may be 100%.
[0036] Furthermore, by controlling the porosity, grain size, and orientation of the crystal grains, the sintered body 100 of the present invention can preferably have a total transmittance of 65% or more for light with a wavelength of 5 μm when the alumina ceramic 120 has a thickness of 900 μm. More preferably, the sintered body 100 of the present invention can have a total transmittance of 70% or more. Naturally, the upper limit may be 100%.
[0037] The sintered body 100 of the present invention may have further alumina ceramics (not shown) on the side facing the alumina ceramics 120 via the polycrystalline spinel ceramics 110. This is expected to further improve mechanical strength. In this case as well, it is preferable that the further alumina ceramics have the same porosity as the alumina ceramics 120 described above, as well as the grain size and orientation of the crystal grains.
[0038] As described above, the sintered body 100 of the present invention has transparency from the visible light to the infrared region and also has excellent mechanical strength, so it can be used as an optical window material for infrared sensors, or as a filter for infrared laser communication and detection applications.
[0039] Next, an exemplary manufacturing method for the sintered body 100 of the present invention, as shown in Figure 1, will be described. Figure 3 is a flowchart showing the manufacturing process of the oriented alumina-layered polycrystalline spinel ceramic sintered body of the present invention.
[0040] Step S310: The polycrystalline spinel raw material powder is compacted to form a polycrystalline spinel molded body. Step S320: Alumina raw material slurry is prepared by dispersing the alumina raw material powder in a dispersion medium. Step S330: While applying a magnetic field, the alumina raw material slurry is molded to form an alumina molded body. Step S340: A polycrystalline spinel molded body and an alumina molded body are laminated to form a laminate. Step S350: The laminate is sintered at a temperature range higher than 1175°C but lower than or equal to 1500°C. As described above, the oriented alumina laminated polycrystalline spinel ceramic sintered body 100 is obtained by sintering a laminate of a compacted polycrystalline spinel molded body and an alumina molded body formed in a magnetic field within a predetermined temperature range. Each step will be described in detail.
[0041] In step S310, there are no particular restrictions on the polycrystalline spinel raw material powder as long as it has the above-described crystalline structure, and commercially available products can be used. The particle size (primary particle diameter) of the polycrystalline spinel raw material powder is preferably in the range of 0.03 μm to 0.35 μm. Using such powder promotes sintering in step S350, making it easier to obtain a dense sintered body. The primary particle diameter is measured by directly measuring the size of the primary particles from electron microscope images. For compaction, methods such as die pressing and cold isostatic pressing (CIP) can be employed. Note that step S310 does not necessarily have to be performed first, but may be performed after step S320 or after step S330.
[0042] In step S310, the density (relative density) of the polycrystalline spinel molded body is preferably in the range of 40% to 70%, more preferably in the range of 50% to 70%. This allows for the sintering in step S350, described later, to yield a sintered body with a sintering density of 96% or more. The density of the polycrystalline spinel molded body is measured by the Archimedes method.
[0043] In step S320, there are no particular restrictions on the alumina raw material powder, and commercially available products can be used. The crystal grains of the alumina raw material powder are composed of single crystals, and are the crystal grains 130 described with reference to Figure 1.
[0044] In step S320, the content of alumina raw material powder in the alumina raw material slurry is preferably in the range of 10% by mass or more and 30% by mass or less. Within this range, the alumina raw material powder can be well dispersed. More preferably, the content of alumina raw material powder is in the range of 15% by mass or more and 25% by mass or less.
[0045] The particle size of the alumina raw material powder is preferably in the range of 0.08 μm to 0.15 μm. Within this range, the alumina raw material powder can be well dispersed in the dispersion medium and is easily oriented in step S330 described later. The particle size of the alumina raw material powder is more preferably in the range of 0.08 nm to 0.12 nm.
[0046] In step S320, the dispersion medium is not particularly limited as long as it disperses the raw material powder, but it is selected to have low viscosity and not react with alumina. The dispersion medium may be water or an organic solvent. Examples of organic solvents include aliphatic hydrocarbons selected from the group consisting of pentane, hexane, heptane, and octane, or alcohols selected from the group consisting of methanol, ethanol, and propanol. These dispersion mediums can promote the dispersion of the alumina raw material powder. Among these, alcohols such as ethanol are preferred.
[0047] In step S320, a polycationic polymer or polyanionic polymer may be further added. This coats the alumina raw material powder particles with the polymer, and the particles are well dispersed by electrostatic repulsion. As a result, in step S330, the rotation of the particles is promoted by the application of a magnetic field, and the oriented sintered body described above can be obtained.
[0048] Examples of polycationic polymers include lyalkylamines (PAM), polyethyleneimines (PEI), polylysine (PL), polypeptides, chitosan, polysaccharides, or copolymers thereof. Examples of polyanionic polymers include ammonium polycarboxylate, polystyrene sulfonate, polyacrylate, polymethacrylate, polyvinyl sulfate, polyphosphate, carrageenan, gellan gum, carboxymethylcellulose, carboxymethyl agarose, carboxymethyl dextran, carboxymethyl chitin, carboxymethyl chitosan, polymers modified with carboxymethyl groups, and alginates.
[0049] The amount of polycationic polymer or polyanionic polymer added may, as an example, be in the range of more than 0% by mass and 5% by mass or less, preferably in the range of more than 0% by mass and 1% by mass or less, and more preferably in the range of more than 0% by mass and 0.5% by mass or less.
[0050] In step S320, an acid or alkali may be added to the alumina raw material slurry. This further improves the dispersion of the particles.
[0051] In step S330, the alumina raw material slurry is formed in a magnetic field to obtain an alumina molded body. The applied magnetic field is preferably in the range of 8T (Tesla) to 14T. Within this range, particle rotation can be promoted. More preferably, the applied magnetic field is in the range of 10T to 14T. Within this range, the particles rotate, and c-axis orientation is further promoted.
[0052] In step S330, the particles of the alumina raw material powder are oriented such that the c-axis of the particles is approximately parallel to the direction of the magnetic field. By utilizing this characteristic, by selecting any direction for the direction of application of the magnetic field, such as a direction parallel to the direction of gravity (vertical direction) or a direction perpendicular to gravity, the orientation direction can be set to correspond to the direction of application of the magnetic field without being limited to the molding direction or shape, and a sintered body that satisfies the orientation relationship described above can be obtained.
[0053] In step S330, various methods may be used for formation (solidification). Solidification methods include slip casting, pressure filtration, tape casting, and electrophoretic deposition. Among these, slip casting or electrophoretic deposition is preferred because it yields a well-oriented alumina molded body with no restrictions on shape. By employing slip casting, a magnetic field can be applied in any direction, even to complex shapes, thus enabling the production of a sintered body with c-axis orientation in any direction.
[0054] In step S330, the density (relative density) of the alumina molded body is preferably in the range of 40% to 70%, more preferably in the range of 50% to 70%. This allows for the subsequent sintering in step S350 to yield a sintered body with a sintering density of 96% or more. The density of the alumina molded body is measured by the Archimedes method.
[0055] Following step S330, the alumina molded body may be pressurized. For pressurization, for example, cold isostatic pressing (CIP) may be used. This allows for the sintering in the subsequent step S350 to yield a high-density sintered body.
[0056] In step S340, the polycrystalline spinel molded body formed in step S310 and the alumina molded body formed in step S330 may be laminated and pressed. In this case as well, for example, cold isostatic pressing (CIP) may be used for pressing. This will provide a good bonding interface, and a high-density sintered body may be obtained by sintering in step S350. In step S340, the laminate may be formed by sandwiching the polycrystalline spinel molded body between a pair of alumina molded bodies.
[0057] In step S350, the sintering of the laminate can be performed in a temperature range of 1175°C to 1500°C or less to obtain a high-density sintered body, but preferably in a temperature range of 1220°C to 1300°C. In this range, a high-density sintered body can be obtained while suppressing grain growth of the crystal grains. More preferably, the sintering is performed in a temperature range of 1225°C to 1275°C. In this range, an even higher density sintered body can be obtained while further suppressing grain growth of the crystal grains.
[0058] In step S350, there are no particular restrictions on the sintering method, and discharge plasma sintering (SPS), atmospheric pressure sintering, hot press (HP) sintering, and hot hydrostatic pressing (HIP) sintering can be used as appropriate. The sintering time varies depending on the sintering method, but for example, when using discharge plasma sintering (SPS), it may be between 5 minutes and 30 minutes.
[0059] In step S350, the molded body may be sintered under pressure to allow for the use of HP sintering or HIP sintering. This may result in a higher density sintered body. As described above, the oriented alumina-layered polycrystalline spinel ceramic sintered body of the present invention can be obtained.
[0060] (Embodiment 2) Embodiment 2 describes an infrared sensor using the alumina-laminated polycrystalline spinel ceramic sintered body of the present invention as an optical window material. Figure 4 is a schematic diagram showing an infrared sensor using the alumina-layered polycrystalline spinel ceramic sintered body of the present invention.
[0061] The infrared sensor 400 of the present invention comprises a package 410, an infrared light receiving unit 420 for detecting infrared rays, and an optical window material 430 positioned to cover it.
[0062] The infrared sensor 400 is an optical device that utilizes a technology in which a light-receiving unit 420 and an optical window material 430 are installed in a package 410, and infrared rays transmitted through the optical window material 430 are converted into electrical signals by the light-receiving unit 420, and the converted information is used. The optical window material 430 is made of the oriented alumina laminated polycrystalline spinel ceramic sintered body 100 described in Embodiment 1. The optical window material 430 has the function of a focusing lens and a protective material for the light-receiving unit, and the sintered body 100 of the present invention is processed into a plate shape, spherical, aspherical, or Fresnel shape. As described above, the sintered body 100 of the present invention has excellent mechanical strength and will not be damaged by processing. Furthermore, because the sintered body 100 of the present invention has excellent mechanical properties and infrared transmittance, it can provide a highly sensitive infrared sensor for use in harsh environments.
[0063] Although Figure 4 shows a specific infrared sensor, the infrared sensor of the present invention is not limited to this, and may be any infrared sensor that employs the sintered body 100 described in Embodiment 1 as the optical window material 430.
[0064] The present invention will now be described in detail using specific examples, but please note that the present invention is not limited to these examples. [Examples]
[0065] [Examples 1-14] Examples 1 through 14 describe the production of various alumina-layered polycrystalline spinel sintered bodies. The manufacturing procedure for Example 2 is described in detail below. Figure 5 shows a procedure illustrating part of the manufacturing process for the sample in Example 2.
[0066] Polycrystalline spinel raw material powder (TSP-15, manufactured by Daimei Chemical Industry Co., Ltd., primary particle size: 0.3 μm) was compacted to form a polycrystalline spinel molded body (step S310 in Figure 3). 700 mg of the polycrystalline spinel raw material powder was packed into a sintering mold with an inner diameter of 10 mm (SL-400, manufactured by Sinterland Co., Ltd.), and a polycrystalline spinel molded body was obtained by uniaxial pressure. At this time, the density (relative density) of the polycrystalline spinel molded body was in the range of 55% to 60%.
[0067] Alumina raw material slurry was prepared by dispersing alumina raw material powder 510 (TM-DAR, manufactured by Daimyo Chemical Industry Co., Ltd., primary particle size: 0.1 μm) in water (ultrapure water) 520 as a dispersion medium and performing ultrasonic treatment (step S320 in Figure 3). The alumina raw material powder content in the alumina raw material slurry was 20% by mass.
[0068] Next, the alumina raw material slurry was molded while a magnetic field was applied to form an alumina molded body (step S330 in Figure 3). The alumina raw material slurry was poured into a slipcast setup consisting of a cylindrical polyethylene mold 550 (φ=12mm, height=40mm) placed on a porous alumina plate 540 covered with a membrane filter 530 (porosity 200nm). To prevent water evaporation, the polyethylene mold 550 was covered with a plastic film 560.
[0069] The slip-cast setup was placed inside a 12T superconducting magnet, and a 12T magnetic field was applied in a direction parallel to the direction of gravity (same as the vertical direction) (arrow indicated by B in Figure 5). At this time, water slowly flowed out through the pores of the membrane filter 530 and the porous alumina plate 540 (arrow indicated by SC in Figure 5). In this way, an alumina molded body 570 was obtained. Next, the alumina molded body 570 was pressurized by CIP at 394 MPa for 10 minutes. The density (relative density) of the molded body at this time was in the range of 55% to 60%.
[0070] A polycrystalline spinel molded body and an alumina molded body were stacked to form a laminate (step S340 in Figure 3).
[0071] The laminate was sintered (step S350 in Figure 3). Sintering was performed by placing the laminate in a sintering mold (φ=10mm), heating it to 1225°C at a heating rate of 5°C / min, and continuing for 10 minutes using an SPS apparatus (LABOX, manufactured by Sinterland Co., Ltd.) while applying a uniaxial pressure of 300 MPa. The sintering temperature was the surface temperature of the sintering mold, measured using an optical pyrometer through a hole drilled in carbon felt. The sintered body obtained in this way was polished and used as the sample for Example 2. For Examples 1 and 3 to 6, sintered bodies were manufactured using the same procedure as in Example 2, referring to the manufacturing conditions shown in Table 1. For Examples 7 to 12, sintered bodies were manufactured using the same procedure as in Example 2, except that a magnetic field of 12T was applied in a direction perpendicular to gravity (vertical direction) (perpendicular to the arrow indicated by B in Figure 5), referring to the manufacturing conditions shown in Table 1.
[0072] In Examples 13 and 14, alumina-laminated polycrystalline spinel ceramic sintered bodies were manufactured using a procedure similar to that described in Non-Patent Document 1. Specifically, 700 mg of polycrystalline spinel raw material powder was placed in a high-pressure sintering mold (SL-400, manufactured by Sinterland Co., Ltd.) with an inner diameter of 10 mm, followed by 200 mg (Example 13) or 400 mg (Example 14) of alumina raw material powder. The laminate was then sintered using an SPS apparatus (LABOX, manufactured by Sinterland Co., Ltd.) under the sintering conditions shown in Table 1, with a uniaxial pressure of 300 MPa applied.
[0073] [Table 1]
[0074] The microstructure of the samples in Examples 1 to 14 was observed using a field emission scanning electron microscope (FE-SEM, SU-8000, Hitachi High-Tech Corporation), and the thickness, grain size, and porosity of the alumina ceramics and polycrystalline spinel ceramics were measured. The grain size and porosity were calculated as described above. Backscattered electron diffraction (EBSD) mapping was also performed using SEM. These results are shown in Figures 6 to 10 and Table 2.
[0075] X-ray diffraction patterns were measured for the samples in Examples 1 to 14. X-ray diffraction was performed using a RINT-2500 diffractometer (manufactured by Rigaku Corporation) with Cu Kα rays, a tube voltage of 40 kV, and a tube current of 300 mA. The results are shown in Figures 11, 15, and Table 3. Furthermore, the change in lattice spacing obtained from the X-ray diffraction method was used to determine sin 2 The residual stress of alumina ceramics was calculated using the ψ method. The results are shown in Table 4.
[0076] Linear transmittance (T) in the wavelength range of 0.25 μm to 1.6 μm for samples in Examples 1 to 14. in The total transmittance (T) in the wavelength range of 2.5 μm to 7 μm for the samples in Examples 1 to 14 was measured using a UV-Vis-Infrared spectrophotometer (SolidSpec-3700DUV, manufactured by Shimadzu Corporation). total The values were measured using a Fourier transform infrared spectrophotometer (FT / IR-6200, manufactured by JASCO Corporation). These results are shown in Figures 12-14, Figure 15, and Table 3.
[0077] The hardness (Hv) of the samples in Examples 1 to 14 was determined using a Vickers hardness tester (MVK-E, manufactured by Akashi Seisakusho Co., Ltd.). The hardness was calculated using the conditions and formula described above. The results are shown in Table 3. The above results will be summarized and explained below.
[0078] Figure 6 shows SEM images of cross-sections of the samples from Example 2 and Example 8. Figure 7 shows an SEM image of the sample from Example 2. Figure 8 shows an SEM image of the sample from Example 8.
[0079] As shown in Figure 6, the cross-sections of the samples in Example 2 and Example 8 showed a two-layer structure of alumina ceramics and polycrystalline spinel ceramics, with no cracks at the interface indicating that the layers were joined together. The thickness of the alumina ceramics was approximately 900 μm, and the thickness of the polycrystalline spinel ceramics was approximately 2400 μm. Although not shown, Examples 3, 5, 9, and 11 exhibited a similar configuration.
[0080] Based on the direction of magnetic field application, as schematically shown in Figure 6, it can be assumed that in the samples of Examples 1 to 6, the c-axis of the alumina crystal grains is oriented perpendicular to the bonding surface of the polycrystalline spinel ceramics, and the a-axis is oriented parallel to the bonding surface of the polycrystalline spinel ceramics, while in the samples of Examples 7 to 12, the c-axis of the alumina crystal grains is oriented parallel to the bonding surface of the polycrystalline spinel ceramics.
[0081] Analysis of the compositional changes at the bonding interface using energy-dispersive X-ray spectroscopy (EDS) from SEM images revealed no presence of a second phase or impurity phase at the bonding interface, indicating that the phases were directly bonded to each other. Furthermore, the EDS analysis profile at the bonding interface gradually changed within the alumina and spinel phases across the interface, suggesting that there may be slight compositional shifts between alumina and spinel, but not enough to alter the crystalline phase.
[0082] As shown in Figures 7 and 8, the samples in Example 2 and Example 8, both alumina ceramics and polycrystalline spinel ceramics, exhibited a dense microstructure with virtually no residual pores. Although not shown, Examples 3, 5, 9, and 11 showed similar characteristics.
[0083] [Table 2]
[0084] As shown in Table 2, it was found that when the sintering temperature is 1175°C or lower, grain growth in polycrystalline spinel ceramics is suppressed, but the porosity of the polycrystalline spinel ceramics increases. Furthermore, when using SPS sintering, it was found that a sintered body with low porosity can be obtained if the upper limit of the sintering temperature is 1300°C.
[0085] Figure 9 shows the EBSD mapping of the samples from Example 2, Example 8, and Example 14. Figure 10 shows the orientation distribution of crystal grains obtained from Figure 9.
[0086] In Figure 9, the data is shown in grayscale, and crystal grains shown at the same brightness indicate that they have the same plane angle from the (0001) plane. The sample in Example 2 contained many alumina crystal grains with the (0001) plane throughout, and it was found that the crystal grains of the alumina ceramics were c-axis oriented approximately perpendicular to the bonding surface with the polycrystalline spinel ceramics. On the other hand, the sample in Example 8 contained many alumina crystal grains with crystal planes that had a plane angle of 90 degrees from the (0001) plane, and the crystal grains in the sample in Example 14 were random.
[0087] Figure 10 plots the inclination θ(°) of the (0001) plane of the alumina crystal grains from 0°, with the direction perpendicular to the bonding surface with the polycrystalline spinel ceramics defined as 0°, for each crystal grain of the sample in Figure 9. Focusing on the sample of Example 2, which was manufactured by applying a magnetic field perpendicular to the surface, it was found that there is a peak at 0°, indicating that the crystal grains of the alumina ceramics are c-axis oriented perpendicular to the bonding surface with the polycrystalline spinel ceramics. Furthermore, more than 50% of the crystal grains of the alumina ceramics were located within ±20° of the peak position. Although not shown, the samples of Example 1 and Examples 3 to 6 showed similar crystal grain orientation distributions.
[0088] Focusing on the sample from Example 8, which was manufactured by applying a magnetic field horizontally, it was found to have a peak at 90°, indicating that the alumina ceramic grains were c-oriented parallel to the bonding surface with the polycrystalline spinel ceramics. Furthermore, more than 50% of the alumina ceramic grains were located within ±20° of the peak position. Although not shown in the figures, the samples from Examples 7 and 9-12 also showed similar grain orientation distributions.
[0089] On the other hand, the alumina ceramic sample of Example 14, which was manufactured without applying a magnetic field, did not show any peaks in its crystal grains. This indicates that the crystal grains of the alumina ceramic are random and unoriented. Although not shown in the figure, the sample of Example 13 also showed a similar crystal grain orientation distribution.
[0090] From these findings, it was found that the sintered body obtained by the manufacturing method shown in Figure 3 comprises polycrystalline spinel ceramics and alumina ceramics bonded thereto. When the orientation relationship of the alumina ceramics was measured by EBSD, the orientation distribution of the alumina ceramic grains showed a peak due to a specific crystal orientation of the alumina ceramic grains being oriented in the range of 0° to 90° with respect to the bonding surface with the polycrystalline spinel ceramics. It was also shown that more than 50% of the alumina ceramic grains oriented in the specific crystal orientation exist within ±20° of the peak position.
[0091] In the experiment, only two magnetic field application directions were used: the same direction as gravity and perpendicular to gravity. However, if the magnetic field is applied at a 45° angle from the direction of gravity, for example, the grain orientation distribution with a peak at 45° is obtained as shown in Figure 10. Those skilled in the art will understand that a sintered body with controlled grain orientation of alumina ceramics can be obtained simply by controlling the direction of the applied magnetic field.
[0092] Figure 11 shows the XRD patterns of the samples from Example 2, Example 8, and Example 13.
[0093] Figure 11 shows the XRD patterns of the alumina ceramics for each sample. As mentioned above, the sample of Example 13, which was manufactured without applying a magnetic field, was unoriented and random. The XRD pattern and peak intensity ratio of the sample of Example 13 were confirmed to match those of ICDD (00-005-0712). On the other hand, the peak intensity ratios of the XRD patterns of the samples of Example 2 and Example 8 did not match those of ICDD. This is because the samples of Example 2 and Example 8, which were manufactured by applying a magnetic field, were oriented.
[0094] Furthermore, focusing on the peak intensities of (006) and (110) in the XRD pattern, the peak intensity ratio I 006 / I 110 Upon investigation, the peak intensity ratio I of the sample in Example 2 was 006 / I 110 The peak intensity ratio was 0.547 for the sample in Example 13, and 0.078 for the sample in Example 13. As mentioned above, the sample in Example 2 is a sintered body in which the crystal grains of alumina ceramics are c-oriented perpendicular to the bonding surface with polycrystalline spinel ceramics, so the peak intensity ratio I 006 / I 110 If the value is 0.25 or higher, it can be simply determined that the crystal grains of the alumina ceramics are c-axis oriented perpendicular to the bonding surface with the polycrystalline spinel ceramics.
[0095] Figure 12 shows the visible light linear transmittance spectra of various samples. Figure 13 shows the infrared transmittance spectra of various samples. Figure 14 shows the infrared transmittance spectra of various samples.
[0096] Figure 12 shows the transmission characteristics of the samples for Examples 2, 8, 13, and 14 for visible light. As shown in Figure 12, the linear transmittance (T) at a wavelength of 500 nm for the samples for Examples 2, 8, and 14, where the alumina ceramic thickness is 900 μm, is shown. in(500nm)The percentages were 28.2%, 20.1%, and 1.2%, respectively, and it was found that the samples of Example 2 and Example 8, in which the crystal grains of alumina ceramics were oriented, had superior transmission properties in visible light compared to the sample of Example 14.
[0097] Furthermore, the linear transmittance (T) at a wavelength of 500 nm for the sample in Example 13, which has an alumina ceramic thickness of 300 μm, is calculated as follows: in(500nm) The transmittance was a large 42.5%, which is because the transmittance of alumina ceramics in the visible light region depends on the thickness of the alumina ceramics, and the transmittance decreases as the thickness increases. From this, it can be seen that if the thickness of the alumina ceramics in the sintered bodies of Example 2 and Example 8 is 300 μm, the transmittance will easily exceed that of the sample in Example 13, resulting in a sintered body with excellent visible light transmission characteristics.
[0098] Furthermore, as shown in Table 3, the samples of Examples 3 and 5, which are sintered bodies in which the crystal grains of alumina ceramics are c-oriented perpendicular to the bonding surface with polycrystalline spinel ceramics, similar to Example 2, exhibited a linear transmittance of over 10% at a wavelength of 500 nm, indicating excellent visible light transmission characteristics. On the other hand, the samples of Examples 1, 4, and 6, which are sintered bodies in which the crystal grains of alumina ceramics are c-oriented perpendicular to the bonding surface with polycrystalline spinel ceramics, similar to Example 2, exhibited a linear transmittance of less than 10% at a wavelength of 500 nm.
[0099] Furthermore, similar to Example 8, the samples in Examples 9 and 11, which are sintered bodies in which the crystal grains of alumina ceramics are c-oriented parallel to the bonding surface with polycrystalline spinel ceramics, exhibited a linear transmittance of over 10% at a wavelength of 500 nm, indicating excellent visible light transmission characteristics. On the other hand, similar to Example 8, the samples in Examples 7, 10, and 12, which are sintered bodies in which the crystal grains of alumina ceramics are c-oriented parallel to the bonding surface with polycrystalline spinel ceramics, exhibited a linear transmittance of less than 10% at a wavelength of 500 nm.
[0100] According to Figures 13, 14 and Table 3, the samples in Examples 2, 3, 5, 8, 9, and 11 all had a total transmittance (T) at a wavelength of 5 μm exceeding 60%. total(5μm) ) was present. The total transmittance at a wavelength of 5 μm for some other samples was below 60%, but it was confirmed that they had relatively good infrared transmittance.
[0101] Even if the crystal orientation of the alumina ceramics grains (e.g., the c-axis) is oriented within a range of 0° to 90° relative to the bonding surface with polycrystalline spinel ceramics, the resulting sintered body does not necessarily exhibit excellent visible light transmission and infrared light transmission. This is thought to be because, as shown in Table 2, the porosity and grain size of the polycrystalline spinel ceramics or alumina ceramics become too large depending on the sintering conditions.
[0102] From this, it can be said that, considering practical application, the porosity of polycrystalline spinel ceramics must be less than 0.3%, the grain size of polycrystalline spinel ceramics must be in the range of 215 nm to 380 nm, the porosity of alumina ceramics must be 0.07% or less, and the grain size of alumina ceramics must be in the range of 320 nm to 680 nm.
[0103] Figure 15 shows the relationship between transmittance and the intensity ratio of X-ray diffraction.
[0104] Figure 15 shows the transmittance at wavelengths of 500 nm and 5 μm, based on the results in Tables 2 and 3, using the peak intensity ratio I. 006 / I 110 This is a plotted figure. As a result, in a sintered body of polycrystalline spinel ceramics satisfying the above-mentioned porosity and grain size, and alumina ceramics bonded thereto that also satisfy the above-mentioned porosity and grain size, the peak intensity ratio of the (006) plane and the (110) plane in the X-ray diffraction pattern of the surface of the alumina ceramics is I 006 / I 110 It was shown that it is preferable for the value to satisfy the range of 0.5 to 0.7.
[0105] [Table 3]
[0106] According to Table 3, a comparison of Examples 1 to 12 with Examples 13 and 14 shows that in sintered bodies formed by bonding alumina ceramics and polycrystalline spinel ceramics, no decrease in mechanical strength was observed even when the crystal grains of the alumina ceramics were oriented to a predetermined configuration, and high mechanical strength was maintained.
[0107] Table 4 shows sin 2 This paper presents the results of investigating the residual stress and state of alumina ceramics located on and bonded to polycrystalline spinel ceramics using the ψ method. A measurement direction of the a-axis means measurements were taken along the a-axis direction of the alumina ceramic grains; a measurement direction of the c-axis means measurements were taken along the c-axis direction of the alumina ceramic grains; and a random measurement direction means the alumina ceramic grains are random and measurements were not taken in a specific crystal direction.
[0108] As a result, when the thermal expansion coefficient in the a-axis direction of the alumina ceramics was investigated using the samples from Example 2 and Example 8, it was found that they had a large positive residual stress, indicating that the alumina ceramics were in a tensile state. From this, it can be said that the thermal expansion coefficient in the a-axis direction of alumina ceramics is larger than that of polycrystalline spinel ceramics.
[0109] On the other hand, when the thermal expansion coefficient in the c-axis direction of alumina ceramics was investigated, it was found that alumina ceramics have a large negative residual stress compared to polycrystalline spinel ceramics, indicating that they are in a compressed state. From this, it can be said that the thermal expansion coefficient in the c-axis direction of alumina ceramics is smaller than that of polycrystalline spinel ceramics.
[0110] In addition, when the thermal expansion coefficient of random alumina ceramics was examined using the sample of Example 14, it was found that it had a negative residual stress with respect to polycrystalline spinel ceramics and the alumina ceramics were in a compressed state. At this time, the magnitude of the absolute value of the residual stress was smaller than that when measured in the c-axis direction. From this, it can be said that the random thermal expansion coefficient of alumina ceramics is smaller than that of polycrystalline spinel ceramics but larger than that in the c-axis direction.
[0111] In summary, the thermal expansion coefficients of alumina ceramics and spinel are c-axis alumina < random alumina < spinel < a-axis alumina in this order. This order is different from the literature values as described above, and it is considered to be due to the orientation and lamination of alumina ceramics. Also, despite such a discrepancy in the thermal expansion coefficients, it can be said that the fact that the mechanical strength was maintained by orienting the alumina ceramics is a surprising result that was not expected.
[0112]
Table 4
Industrial Applicability
[0113] The oriented alumina laminated polycrystalline spinel ceramic sintered body of the present invention not only has excellent permeability in a wide band from visible to mid-infrared but also has high hardness. Therefore, in addition to optical window materials such as infrared sensors that require scratch resistance, heat resistance, corrosion resistance, and durability, it can be applied to industrial uses such as watch window materials, light source window materials, window materials for manufacturing equipment used in high-temperature or plasma environments, and filters for infrared laser communication and detection applications.
Explanation of Symbols
[0114] 100 Oriented alumina laminated polycrystalline spinel ceramic sintered body 110 Polycrystalline spinel ceramics 120 Alumina ceramics 120A, 120B Oriented Alumina Ceramics 130 crystal grains 400 Infrared Sensors 410 packages 420 Infrared Receiver 430 Optical window material 510 Alumina raw material powder 520 Water (ultra pure water) 530 Membrane Filter 540 Porous Alumina Plate 550 Cylindrical polyethylene molds 560 Plastic Film 570 Alumina molded body
Claims
1. Polycrystalline spinel ceramics and an alumina ceramic located on the polycrystalline spinel ceramic and bonded to the polycrystalline spinel ceramic; Equipped with the polycrystalline spinel ceramic has a porosity of less than 0.3%; The grain size of the polycrystalline spinel ceramic is in the range of 215 nm to 380 nm, The porosity of the alumina ceramic is 0.07% or less, The grain size of the alumina ceramic is in the range of 320 nm to 680 nm, An oriented alumina-laminated polycrystalline spinel ceramic sintered body, in which, when the orientation relationship of the alumina ceramic is measured by electron backscatter diffraction (EBSD) method, the orientation distribution of the crystal grains of the alumina ceramic has a peak due to a specific crystal orientation of the crystal grains of the alumina ceramic being oriented in the range of 0° or more and 90° or less with respect to the joint surface with the polycrystalline spinel ceramic, and 50% or more of the crystal grains of the alumina ceramic oriented in the specific crystal orientation are present within a range of ±20° from the position of the peak.
2. 2. The oriented alumina layered polycrystalline spinel ceramic sintered body according to claim 1, wherein the porosity of the polycrystalline spinel ceramic is in the range of 0.05% or more and 0.2% or less.
3. 3. The oriented alumina layered polycrystalline spinel ceramic sintered body according to claim 2, wherein the porosity of the polycrystalline spinel ceramic is in the range of 0.1% or more and 0.2% or less.
4. 2. The oriented alumina laminated polycrystalline spinel ceramic sintered body according to claim 1, wherein the alumina ceramic has a porosity in the range of 0.04% or more and 0.07% or less.
5. 2. The oriented alumina layered polycrystalline spinel ceramic sintered body according to claim 1, wherein the grain size of the crystal grains of the polycrystalline spinel ceramic is in the range of 230 nm to 365 nm.
6. 2. The oriented alumina laminated polycrystalline spinel ceramic sintered body according to claim 1, wherein the grain size of the crystal grains of the alumina ceramic is in the range of 340 nm to 660 nm.
7. 2. The oriented alumina laminated polycrystalline spinel ceramic sintered body according to claim 1, wherein when the thickness of the alumina ceramic is 900 μm, the linear transmittance of the polycrystalline spinel ceramic for light having a wavelength of 500 nm is 13% or more.
8. 2. The oriented alumina laminated polycrystalline spinel ceramic sintered body according to claim 1, wherein when the thickness of the alumina ceramic is 900 μm, the total transmittance of the polycrystalline spinel ceramic for light having a wavelength of 5 μm is 65% or more.
9. 2. The oriented alumina laminated polycrystalline spinel ceramic sintered body according to claim 1, wherein the orientation distribution of crystal grains of said alumina ceramic has a peak at 0° or 90° to the joint surface with said polycrystalline spinel ceramic.
10. The peak intensity ratio I between the (006) plane and the (110) plane in the X-ray diffraction pattern of the surface of the alumina ceramic 006 / I 110 The oriented alumina laminated polycrystalline spinel ceramic sintered body according to claim 9, wherein is in the range of 0.5 or more and 0.7 or less.
11. Equipped with additional alumina ceramics, the further alumina ceramic is bonded to the polycrystalline spinel ceramic on a side opposite to the alumina ceramic; The porosity of the further alumina ceramic is 0.07% or less; The grain size of the crystal grains of the further alumina ceramic is in the range of 320 nm to 680 nm, 2. The oriented alumina-laminated polycrystalline spinel ceramic sintered body according to claim 1, wherein, when the orientation relationship of the further alumina ceramic is measured by electron backscatter diffraction (EBSD) method, the orientation distribution of crystal grains of the further alumina ceramic has a peak due to a specific crystal orientation of the crystal grains of the further alumina ceramic being oriented in a range of 0° to 90° with respect to the joint surface with the polycrystalline spinel ceramic, and 50% or more of the crystal grains of the further alumina ceramic oriented in the specific crystal orientation are present within a range of ±20° from the position of the peak.
12. compacting the polycrystalline spinel raw material powder to form a polycrystalline spinel compact; Dispersing an alumina raw material powder in a dispersion medium to prepare an alumina raw material slurry; forming an alumina compact by forming the alumina raw material slurry while applying a magnetic field; stacking the polycrystalline spinel compact and the alumina compact to form a laminate; sintering the laminate at a temperature in the range of 1175° C. to 1500° C.; The method for producing an oriented alumina laminate-type polycrystalline spinel ceramic sintered body according to any one of claims 1 to 11, comprising:
13. The method of claim 12 , wherein forming the alumina compact uses slip casting or electrophoretic deposition.
14. 13. The method of claim 12, wherein the stack is a polycrystalline spinel compact sandwiched between a pair of alumina compacts.
15. 13. The method of claim 12, wherein the density of the polycrystalline spinel compact and the alumina compact is in the range of 40% or more and 70% or less.
16. The method of claim 12, wherein the sintering comprises sintering the laminate at a temperature in the range of 1220°C to 1300°C.
17. An optical window material comprising the oriented alumina layered polycrystalline spinel ceramic sintered body according to any one of claims 1 to 11.
18. An infrared sensor comprising the optical window material according to claim 17.
19. A filter comprising the oriented alumina laminated polycrystalline spinel ceramic sintered body according to any one of claims 1 to 11.